RELIGIOUS FREEDOM AND ITS DIMENSIONS IN THE PROPHETIC ERA AN ANALYTICAL STUDY - Bayati, Abdul Jabbar Star AL (International Journal of Psychosocial Rehabilitation, 2020)
The study dealt with the issue of religious freedom in the era of the message, and the statement of evidence and truth and practice, which is one of the priorities of the call of the prophets and messengers, and was the main slogan of each Prophet and the Prophet, and was the first premise in his call  in Mecca, and the study aims to identify the methodology of the Prophet in dealing with the owners The other religions are individuals and societies through the administration of the state, starting from the document Medina, which is the first constitution of the Islamic state, to show us the extent of his concern to co-exist with each other and to be a guide and a way of life for those engaged in Islamic work in our contemporary reality.